Quality of life among Indonesian family caregivers caring for dependent older persons with type 2 diabetes mellitus in the community: A cross-sectional, correlational study - Siregar, Rinco; Kritpracha, Charuwan; Chinnawong, Tippamas; Latour, Jos M. (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: The global prevalence of older adults with diabetes has increased, and family caregivers in Indonesia play a critical role in managing diabetes and providing personal care. However, caregiving can be complex and challenging, often negatively affecting caregivers' quality of life (QoL). Objective: This study aimed to develop and test a hypothesized causal model of QoL among Indonesian family caregivers who care for dependent older persons with type 2 diabetes mellitus (T2DM) in 2024. Methods: A cross-sectional, correlational study was conducted with 270 family caregivers recruited from five Community Health Centers. Data were collected using various scales: the Center for Epidemiologic Studies Depression Scale, the Zarit Burden Interview, the Duke University Religion Index, the Perceived Knowledge on T2DM Care Scale, the Family-Carer Diabetes Management Self-Efficacy Scale, the Multidimensional Scale of Perceived Social Support, and the Quality-of-Life Index. Descriptive statistics and Partial Least Squares Structural Equation Modeling (PLS-SEM) were used for analysis. Results: The final model explained 89.1% of the variance in the quality of life (QoL) of family caregivers (R² = 0.893, Adjusted R² = 0.891), with 66% predictive relevance. Depression symptoms had the strongest negative direct effect on QoL, followed by caregiver burden. Self-efficacy and perceived knowledge had positive direct effects, while social support showed no significant direct effect. Indirect effects revealed that social support and self-efficacy positively influenced QoL through depression symptoms. The total effect (TE) analysis confirmed that depression symptoms had the strongest negative effect on QoL (TE = -0.744, p <0.001), while social support (TE = 0.443, p <0.001) and self-efficacy (TE = 0.413, p <0.001) had positive effects. Conclusion: Reducing depression symptoms and caregiver burden, strengthening social support, and promoting self-efficacy could significantly improve the QoL of family caregivers who care for older persons with T2DM. Nursing practice should address caregivers' physical and emotional needs, provide education, foster social support, and support caregiver mental health.